2007
DOI: 10.1016/j.neuroscience.2007.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 depresses solitary tract-mediated synaptic transmission in the nucleus tractus solitarius

Abstract: Prostaglandin E 2 (PGE 2 ) is a prototypical inflammatory mediator that excites and sensitizes cell bodies (Kwong and Lee, 2002; and peripheral nerve terminals (Ho et al. 2000) of primary vagal sensory neurons. Nearly all central nerve terminals of vagal afferents are in the nucleus tractus solitarius (NTS), where they operate with a high probability of release (Doyle and Andresen, 2001). We studied the effect of PGE 2 on synaptic transmission between tractus solitarius afferent nerve terminals and the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
2
13
1
Order By: Relevance
“…We specifically tested monosynaptic RVLM-projecting cells, and found that bath application of the non-NMDA receptor antagonist CNQX abolished TS evoked EPSCs and sEPSCs. Thus, similar to CVLM-projecting nTS neurons (Bailey et al, 2006; Li and Yang, 2007) and other second-order nTS cells (Chen et al, 1999; Doyle and Andresen, 2001; Kline et al, 2002; Laaris and Weinreich, 2007), non-NMDA receptors appear to mediate the majority of excitatory inputs to RVLM-projecting nTS cells.…”
Section: Discussionmentioning
confidence: 85%
“…We specifically tested monosynaptic RVLM-projecting cells, and found that bath application of the non-NMDA receptor antagonist CNQX abolished TS evoked EPSCs and sEPSCs. Thus, similar to CVLM-projecting nTS neurons (Bailey et al, 2006; Li and Yang, 2007) and other second-order nTS cells (Chen et al, 1999; Doyle and Andresen, 2001; Kline et al, 2002; Laaris and Weinreich, 2007), non-NMDA receptors appear to mediate the majority of excitatory inputs to RVLM-projecting nTS cells.…”
Section: Discussionmentioning
confidence: 85%
“…Alternate means of IL-1β activation of TH neurons include relayed messages from other neurons or glial cells. Other researchers have recently shown that exposure to PGE 2 —a downstream product of IL-1β stimulation in glial cells—modulated neuronal electrical activity in the NTS, suggesting that glial cell production of PGE 2 in response to IL-1β may be the means by which TH neurons are activated [19,26]. Further experiments will be required to investigate whether TH neurons are activated by PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II (Barnes et al, 2003), substance P (Sekizawa et al, 2003; Bailey et al, 2004), enkephalins (Glatzer and Smith, 2005), adenosine/ATP (Kato and Shigetomi, 2001; Shigetomi and Kato, 2004), prostaglandin E2 (Laaris and Weinreich, 2007) and norepinepherine (Zhang and Mifflin, 2007) alter neurotransmitter release, postsynaptic activity, or the magnitude of synaptic depression. Dopamine also reduces TS-evoked glutamate release to induce synaptic depression in the NTS (Kline et al, 2002).…”
Section: Short-term Synaptic Plasticitymentioning
confidence: 99%